A biographical dictionary of dissenting economists - Arestis, Philip; Sawyer, Malcolm C. (Cheltenham, UK ; Northampton, MA : E. Elgar, 2000)
This publication is an extensive and authoritative guide to economists both past and present, providing biographical, bibliographical and critical information on over one hundred economists working in the non-neoclassical traditions broadly defined. It includes entries on, amongst others, radical economists, Marxists, post-Keynesians, behaviourists, Kaleckians and institutionalists. The book demonstrates the extent and richness of the radical heterodox tradition in economics.
Includes bibliographical references.
ne 28/09/2021
Ref.
Keywords: Economists